2022
DOI: 10.1155/2022/6837745
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Immunity of Patients with Tuberculosis Combined with Diabetes

Abstract: Tuberculosis (TB) is one of humanity’s three major infectious diseases. Diabetes mellitus (DM) is a metabolic disease characterized by hyperglycemia due to impaired insulin secretion or impaired insulin function. It has been reported that DM is a primary risk factor for TB disease. Given the increasing public health threat to people’s health, more and more studies have focused on diabetes complicated by TB. Hyperglycemia can affect the function of human immune cells, promote primary infections and reactivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Similarly, DC has the strongest antigen commission capacity, and its total population was maintained at 200 cells/mm 3 ( Figure 6B ). T cell immune response significantly eliminates MTB, of which CD4 + T cells are vital ( 52 ). The results showed that the population of total TH cells increased significantly in immunization simulations and peaked in the third injection, and the memory and non-memory TH cell peaks were 12,000 cells/mm 3 and 95,000 cells/mm 3 , respectively ( Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, DC has the strongest antigen commission capacity, and its total population was maintained at 200 cells/mm 3 ( Figure 6B ). T cell immune response significantly eliminates MTB, of which CD4 + T cells are vital ( 52 ). The results showed that the population of total TH cells increased significantly in immunization simulations and peaked in the third injection, and the memory and non-memory TH cell peaks were 12,000 cells/mm 3 and 95,000 cells/mm 3 , respectively ( Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that there is a distinct evolution of the inflammatory process in subjects with APTB compared to those with TBDM when receiving the standard anti-TB treatment. This is due to the possible influence of DM on the immune response to TB and its effects on the different elements of the cytokine network during the immune response, as mentioned above [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…DM decreases the IFN- γ level [ 57 , 58 ] as well as the antigen-presenting ability of macrophages. IL-8 and IL-22 drop in case of TB-DM co-disease state affecting phagocytosis and TB clearance [ 59 ].…”
Section: Discussionmentioning
confidence: 99%